The Role of Key Opinion Customers and Key Opinion Leaders in Purchasing Decisions for Scarlett Skincare Products on TikTok Shop - Miftah Emilia Zarwati; Nabila Putri Maharani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the impact of Key Opinion Customers (KOC) and Key Opinion Leaders (KOL) on purchasing decisions for Scarlett skincare products through the TikTok Shop platform. The approach used is quantitative, employing a survey method through a questionnaire distributed to respondents selected based on specific criteria, namely active TikTok users in Lampung Province who have viewed KOC or KOL content related to Scarlett products and have used the products. The research instrument has undergone validity and reliability testing and has been deemed suitable for use. The analysis results indicate that KOC has a positive and significant impact on purchasing decisions, meaning that authentic consumer experiences can increase user interest and confidence in purchasing products. In addition, KOL has also been proven to have a positive and significant impact, where the delivery of information by public figures helps strengthen consumer considerations in choosing products. Simultaneously, both variables indicate an important contribution to purchasing decisions, although there are still other aspects outside the scope of this study that also play a role. Overall, this study confirms that KOC and KOL have a strategic role in influencing the purchasing behavior of Scarlett skincare products on TikTok Shop.